2001
DOI: 10.1081/pln-100103782
|View full text |Cite
|
Sign up to set email alerts
|

Fallow Versus Wheat Cropping of Unamendedand Manure-Amended Soils Related to Mycorrhizal Colonization, Yield, and Plant Nutrition of Dry Bean and Sweet Corn

Abstract: Previous studies reported manure application to eroded Portneuf silt loam soil (Coarse-silty, mixed, superactive, Durinodic Xeric Haplocalcid) improved dry bean (Phaseolus vulgaris L., cv. Viva) yield to levels of topsoil. These yield increases only correlated with whole-plant zinc (Zn) concentration and soil organic matter. This might be related to enhanced arbuscular mycorrhizal (AM) colonization stimulated by manure application. A greenhouse study with dry bean suggested a relationship between manure applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 35 publications
(64 reference statements)
0
4
0
2
Order By: Relevance
“…Similarly, Ryan and Angus (2003) reported that AM colonization was decreased by growing corn after canola, a nonhost crop, or through maintenance of bare fallow with herbicides or tillage. The reduced AM colonization rate can be attributed to the reduction of AM hyphal propagules in the previously fallow soils (Allen et al, 2001; Kabir et al, 1999; Thompson, 1987), slowing the early season colonization.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Ryan and Angus (2003) reported that AM colonization was decreased by growing corn after canola, a nonhost crop, or through maintenance of bare fallow with herbicides or tillage. The reduced AM colonization rate can be attributed to the reduction of AM hyphal propagules in the previously fallow soils (Allen et al, 2001; Kabir et al, 1999; Thompson, 1987), slowing the early season colonization.…”
Section: Resultsmentioning
confidence: 99%
“…The benefit of organic amendments on AM fungi has been attributed to increased porosity, enlarged mean weight diameter of aggregates, improved water retention capacity, greater activity of beneficial soil microbes, increased crop rooting, and a better distribution of nutrients in the soil profile (Celik et al, 2004). However, Ellis et al (1992) and Allen et al (2001) found that AM colonization was inconsistently affected by manure applications.…”
mentioning
confidence: 99%
“…Colonization of roots followed the same pattern as the growth of AM fungi hyphae. In contrast, Allen et al (2001) reported a greater AM colonisation of dry bean and sweet corn in unamended than in manured soils.…”
Section: Phosphorusmentioning
confidence: 77%